Dampak Stres Kerja, Dukungan Sosial, dan Keseimbangan Kehidupan Kerja terhadap Kepuasan Kerja - Febriyan Muliany; Try Wahyu Utami; Zakhi Bailatul Nur Avian; Ahmad Salabi; Najmi Ismail (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The role of employees in a company organization is a very vital factor in achieving and carrying out the functions and objectives of the company. Employees become planners, implementers, and controllers who always play an active role in realizing the goals of the organization or industry. In this study, this study uses a quantitative research type. This study aims to determine the effect of work stress, social support, and work-life balance on job satisfaction. This study focuses on company employees in Indonesia, by applying the Non-Probability Sampling technique to determine the sample obtained as many as 120 respondents. The results of this study found that work stress, social support, and work-life balance have an effect on job satisfaction.